Neck circumference as an independent indicator of visceral obesity in a Chinese population - Li Zhao; Guolan Huang; Fangzhen Xia; Qin Li; Bing Han; Yi Chen; Chi Chen; Dongping Lin; Ningjian Wang; Yingli Lu (Lipids in Health and Disease, 2018)
Abstract Background Neck circumference (NC) was reported to be associated with visceral obesity in some specific subjects. However, no studies have reported whether NC could identify visceral obesity in the general population. Here, we mainly aimed to explore whether NC is suitable to identify visceral obesity in the general population. Methods Our data were from a cross-sectional survey on the prevalence of metabolic diseases and risk factors in East China from 2014 to 2015. A total of 9366 participants aged 18–93 were identified for analysis. Anthropometric indices, biochemical parameters and clinical characteristics were measured. The NC values were quartered according to sex. Spearman’s correlation coefficient was employed to test the correlations between different variables. Linear regression and logistic regression were conducted to explore the relationship of NC with visceral adiposity indices and visceral obesity. Results Among the 9366 participants, 3938 (42.05%) were male and 5428 (57.95%) were female. NC had a positive correlation with the visceral adiposity indices, regardless of sex. In all quartiles of NC, in both men and women, as NC values increased, the values of all the fatness indices showed a tendency to increase (all P < 0.001). After full adjustment for demographic variables and metabolic factors, linear regression showed that NC was still associated with the fatness indices for visceral obesity (all P < 0.001). In addition, logistic analysis showed that a larger NC was associated with a higher risk of visceral obesity in both males (OR 32.34, 95% CI 24.02–43.53; P < 0.001) and females (OR 21.43, 95% CI 17.30–26.55; P < 0.001) after adjusting for potential confounding factors. Conclusion NC can be a supplemental indicator for identifying visceral obesity in the general Chinese population.